FEATURES OF RETRACTION IN THE PRODUCTION OF AESTHETIC CONSTRUCTIONS - D.D. Kindiy; V.D. Kindiy; D.M. Korol; K.D. Toncheva; O.S. Shemetov; R.V. Petrenko (Український стоматологічний альманах)
The authors of the article studied and analyzed scientific literary sources for gingival retraction in orthopedic interventions in the case of aesthetic prosthetics. The types and means of retraction, its positive aspects and negative influence on gums are also analyzed. The necessity of carrying out of this manipulation, considering the features of the structure of the gums, has been established.